Multidisciplinary treatment for macrometastatic osteogenic sarcoma. Issue 6043 (30th October 1976) - Jaffe, N; Traggis, D; Cassady, J R; Filler, R M; Watts, H; Frei, E
Abstract : Using a co-ordinated multidisciplinary approach with surgery, radiation therapy, and chemotherapy, 14 out of 21 patients with metastases from osteogenic sarcoma were rendered free of disease for over two to over 18 months. Most patients had pulmonary metastases, two had bony metastases, and one had metastases in the iliac nodes. As part of this multidisciplinary approach weekly high-dose methotrexate was given and caused tumour regression in seven out of 15 patients. After all clinical evidence of disease had been removed high-dose methotrexate was administered every two to three weeks as maintenance treatment. To assess the efficacy of treatment the results were compared with those in a historical control group of 82 consecutive patients who developed pulmonary or other metastases. The results in the study group were significantly better. This experience may be similar to that in Wilms's tumour, where actinomycin D has increased the cure rate when administered as adjuvant therapy after treatment of localised or overt metastatic disease.